Upaya Meningkatkan Minat Belajar Siswa pada Mata Pelajaran IPS dengan Menggunakan Pendekatan Paikem di Kelas IV SDN 097522 Siantar - Wahyu Hidayat (Medan Resource Center, 2023)
This study addresses the issue of low student interest in math learning and aims to enhance their engagement through the implementation of the Participatory Learning and Knowledge Exchange Model (PALKEM) approach. The research focuses on a sample of 15 fifth-grade students, consisting of 7 boys and 8 girls, with the objective of investigating the impact of the PALKEM approach on student learning. The findings reveal a significant increase in student interest during the instructional cycles, with all 15 students (100%) demonstrating heightened engagement. These outcomes suggest that the utilization of the PALKEM approach effectively enhances students' interest in math learning. The results provide promising implications for improving students' motivation and involvement in the subject matter, specifically within the context of the LPS (math) curriculum. Therefore, the PALKEM approach emerges as a potential solution for addressing the issue of low interest in math learning and promoting a more engaging and effective learning environment.